Global Relative Poverty - Nielsen, Lynge (Washington, D.C. : International Monetary Fund, 2009)
The paper provides estimates of global relative poverty trends from 1970 onwards. Relative poverty is shown to have decreased significantly, but at the same time there has been a worsening poverty outcome among up to one billion of the world's poorest citizens. The paper also proposes a straightforward method for dividing an income distribution into classes of poor, rich, and middle-class.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet